2021
DOI: 10.4236/wja.2021.113009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV, HBV and HCV Infections among Sickle Cell Disease Patients in Southwestern Nigeria: A Case-Control Study

Abstract: Aim: This study was designed to determine the prevalence of HBV, HCV and HIV infections among individuals with Sickle Cell Disease (SCD) in Ibadan, southwestern Nigeria. Methodology: In this case-control study, 1017 patients with SCD and 1017 age and gender matched controls were enrolled from 6 health facilities and some communities in Ibadan, southwestern Nigeria. Blood samples were tested for the presence of HIV, HBV and HCV infections. Structured questionnaire was used to capture participants' information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…The decreasing trend in the prevalence of HBV, HCV, and HIV in our study, which generally agree with previous epidemiological reports from the state and national health statistics could be attributed to the positive influence of various national health education programs aimed at reducing blood-borne and sexually transmitted infections in the country. Our findings support the report of Odaibo et al (2021) which attributed the increased availability of vaccines for HBV, prevention of mother-to-child transmission programs for HIV, and nationwide improvement in the screening of blood for transfusion to the widespread report of low prevalence HBV, HIV, and HCV infections in different epidemiological investigations.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The decreasing trend in the prevalence of HBV, HCV, and HIV in our study, which generally agree with previous epidemiological reports from the state and national health statistics could be attributed to the positive influence of various national health education programs aimed at reducing blood-borne and sexually transmitted infections in the country. Our findings support the report of Odaibo et al (2021) which attributed the increased availability of vaccines for HBV, prevention of mother-to-child transmission programs for HIV, and nationwide improvement in the screening of blood for transfusion to the widespread report of low prevalence HBV, HIV, and HCV infections in different epidemiological investigations.…”
Section: Resultssupporting
confidence: 91%
“…Previously, a similar study among undergraduate students in Rivers and Kogi State documented HCV prevalence of 0% (Okonko et al, 2014) and 4.5% (Omatola et al, 2016), respectively. The current HIV prevalence rate is comparable with a 0.3% anti-HIV seropositivity rate recently reported by Odaibo et al (2021) among Sickle Cell Disease individuals in southwestern Nigeria but substantially lower than the 3.3% prevalence rate reported for Kogi State by the Ministry of Health in 2015 (FMH, 2015). The findings of this study corroborate previous epidemiological national health data which indicated a clear decline in national HIV prevalence of 2.8% in 2018; 1.4% in 2019 (FMH, 2019).…”
Section: Resultssupporting
confidence: 74%
“…The prevalence of HIV, HBV and HCV in mono, dual or triple infection has been reported in several populations in Nigeria including Sickle Cell Disease Patients 15 , pregnant women 16 , blood donors 17 , healthcare workers 18 , sex workers 19 and men who have sex with men including transgenders 20 . However, there is paucity of information on coinfection of these viruses among livestock merchants and slaughterhouse workers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the World Health Organization (WHO) targets for the eradication of Hepatitis B as a public health problem by 2030, death attributable to Viral Hepatitis has continued to increase over the past decades with sub-Saharan Africa accounting for 20-30% of persons living with Hepatitis B Infection [1]. Hepatitis B virus is a common transfusion transmitted infection and among the most frequent complications in individuals with Sickle Cell Disease (SCD) due to their life-long dependent on transfusion therapy and uncertainties in donor blood testing procedures [2,3]. Efforts to reduce the incidence and prevention of HBV infection in Nigeria are limited even though an effective vaccine has been available in the country since 2004 [4].This implies that persons who were born before 2004 had no opportunities of being vaccinated with an unquantifiable proportion of such persons who has been living with the infection constituting a reservoir of infection [4].…”
Section: Introductionmentioning
confidence: 99%